2023
DOI: 10.13189/saj.2023.110112
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Psychometric Investigation of a Chinese Version of Athlete Engagement Questionnaire (AEQ)

Abstract: Athlete engagement is one of the key indicators of athletes' positive psychology. It plays a crucial role in coping with burnout and disengagement, creating a flow experience, and improving their competitive ability and performance. In the last two decades, a mountain of literature has focused on engagement in different research settings. In the world of sports, the Athlete Engagement Questionnaire (AEQ) has been proven to be a reliable instrument to access athletes' engagement at both amateur and elite levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…While previous validations have demonstrated that the model is invariant by gender [ 23 , 28 ] and across different competitive levels [ 25 ], the effects of athletes’ age and its interactions on engagement have not been examined in previous literature. Therefore, multivariate analyses were conducted, revealing that male athletes reported significantly higher levels of confidence compared to female athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous validations have demonstrated that the model is invariant by gender [ 23 , 28 ] and across different competitive levels [ 25 ], the effects of athletes’ age and its interactions on engagement have not been examined in previous literature. Therefore, multivariate analyses were conducted, revealing that male athletes reported significantly higher levels of confidence compared to female athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Since the creation of the Athlete Engagement Questionnaire (AEQ), it has been translated, adapted, and validated in several countries, including Portugal [22,23], Croatia [24], Spain [10,25,26], Turkey [27], and China [28], and has also been used in athletes from Sweden [12]. The psychometric properties of the various AEQ versions are presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…s-EMBU-C compiled by Swedish psychiatric expert Perris and amended by domestic Jiang jiang et al [7]. Jiang Jiang was adopted, with two sets of father version and mother version [8]. The contents of the two versions of the questionnaire were the same except that the object of the questionnaire was father and mother.The single questionnaire consisted of 21 questions and 42 projects, three dimensions: emotional warmth, rejection and overprotection.…”
Section: Methodsmentioning
confidence: 99%
“…Since the reform and opening up, unlike the "class" in the West, which divides finance and power as the standard, the "class" is more inclined to bring a series of benefits to social and economic development, and to take "production relations as the basis for division". There are different degrees of stratification, which has resulted in the phenomenon of stratification, and the proportion of medium-sized income groups has increased significantly, and the level of development gap between urban and rural areas has been significantly reduced by all members of society according to reputation, power and wealth and the living standards of residents [5]. In China, the middle class is the majority of the population, and they have a lot of education problems, especially about education anxiety and education expectations.…”
Section: Literature Reviewmentioning
confidence: 99%